PRICE TRANSMISSION ANALYSIS OF RED CHILI PEPPERS (Capsicum annuum L.) IN ACEH PROVINCE - Maulana, Oki; Indra, Indra; Kasimin, Suyanti (CV. Radja Publika, 2023)
For horticultural commodities in general, the role of marketing for red chili commodities makes an important contribution in improving the performance of red chili commodity farming as a whole considering the unique characteristics of horticultural commodities in general such as perishability, perishability, volumenious, production is seasonal while consumption occurs throughout the year. Red chili marketing from farmers to the consumer level, the interaction between marketing agencies becomes important in forming prices. Producing farmers still seem to face price fluctuations, especially during harvest, and it is traders who have more access to obtain higher prices. The purpose of this research is to analyze the price transmission pattern of red chili at the producer level, wholesalers and consumers as well as analyzing what factors influence the formation and movement of red chili prices at the level of red chili producers, wholesalers and consumers in Aceh Province. The results of the study, during 2017-2021 the transmission of red chili prices took place indirectly, meaning that there was a short-term asymmetry at the level of producers to wholesalers and wholesalers to producers. One of the factors causing price formation to occur in the period 2017-2021 is the available supply, while the price of fuel oil is not significant because the price of changes in fuel oil does not fluctuate except at the end of 2021 until now. During 2017-2021 the transmission of red chili prices took place indirectly, meaning that there was a short-term asymmetry at the producer to wholesale and wholesale to producer levels. One of the factors causing price formation to occur in the period 2017-2021 is the available supply, while the price of fuel oil is not significant because the price of changes in fuel oil does not fluctuate except at the end of 2021 until now. During 2017-2021 the transmission of red chili prices took place indirectly, meaning that there was a short-term asymmetry at the producer to wholesale and wholesale to producer levels. One of the factors causing price formation to occur in the period 2017-2021 is the available supply, while the price of fuel oil is not significant because the price of changes in fuel oil does not fluctuate except at the end of 2021 until now.